AN ANALYSIS OF STUDENTS' DIFFICULTIES IN WRITING ANALYTICAL EXPOSITION TEXTS BY THE SECOND YEAR STUDENTS OF SMA N 13 PEKANBARU - Septiani, Syafira; Prawati, Atni; Eliwarti, Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This descriptive research is aimed to find out the students' difficulties in writing Analytical Exposition Texts at the second-year students of SMA N 13 Pekanbaru and to analyze the students’ difficulties in writing Analytical Exposition Text at the second-year students of SMA N 13 Pekanbaru. The population of this research was the second year students of SMA N 13 Pekanbaru in the academic year of 2019/2020. The samples were the students of XI. MIA 1 consists of 30 students who have been selected using cluster random sampling technique. The data were collected by using writing test and interview. The writing tests were analyzed using a writing assessment by Hughes (1989), and the interviews were analyzed by counting the most answers. As a result of the research, it was found that the second year students’ difficulties in writing analytical exposition text were classified as fair (63, 9). The second year students’ difficulties were found in the aspect of the organization (51, 8) and mechanic (56). Thus, in other words, it can be concluded that students’ difficulties in writing analytical exposition texts by the second year students of SMA N 13 Pekanbaru were classified into fair (63.9) and the students’ difficulties were in the aspect of organization and mechanic.Key Words: Analysis, Difficulties, Writing, Analytical Exposition Text.